(untitled) (Research, Society and Development, 2023)
Objective: to map care recommendations from the SBAR tool during the shift change by the health team in inpatient units to support the safety of adult patients in the transition of care. Method: this is a scoping review, carried out in six databases, including publications between January 2017 and January 2022. Based on recommendations from Preferred Reporting Itens for Systematic Reviews and MEta-Analyses extension for Scoping Reviews (PRISMA-ScR). Results: of the 17 studies identified, 35.3% were published in 2020, in the CINAHL database (29.4%). The country that stood out in number of publications was the United States with 41.20%. As for the recommendations for the development of handover instruments, it was identified that they should be clear, simple and sequential. The use of five domains is suggested: patient identity, current situation, clinical history, system status review and recommendations. With regard to the team that conducts the main strategies, its focus is on preparing the environment, training for the use of standardization and minimizing noise in communication. Conclusion: the study shows important recommendations capable of subsidizing the shift change and minimizing the risk of adverse events, in order to strengthen patient safety.